Strong nonlinear terahertz response induced by Dirac surface states in Bi2Se3 topological insulator - Flavio Giorgianni (Nature Portfolio, 2016)
The terahertz response of topological insulator surface states, in which relativistic electrons are protected from backscattering, possesses potential optic and plasmonic applications. Here, the authors demonstrate a nonlinear absorption response of Bi2Se3to terahertz electric fields.